Role of DNA de novo (de)Methylation in the Kidney in Salt-Induced Hypertension - Liu, Pengyuan (Hypertension, 2018)
Numerous adult diseases involving tissues consisting primarily of non-dividing cells are associated with changes in DNA methylation. It suggests a pathophysiological role for de novo methylation or demethylation of DNA, which is catalyzed by DNA methyltransferase 3 (Dnmt3) and ten-eleven translocases (Tet). However, the contribution of DNA de novo (de)methylation to these diseases remains almost completely unproven. Broad changes in DNA methylation occurred within days in the renal outer medulla of Dahl SS rats fed a high-salt diet, a classic model of hypertension. Intra-renal administration of anti-Dnmt3a/Tet3 GapmeR’s attenuated high salt-induced hypertension in SS rats. The high salt diet induced differential expression of 1,712 genes in the renal outer medulla. Remarkably, the differential expression of 76% of these genes were prevented by anti-Dnmt3a/Tet3 GapmeR’s. The genes differentially expressed in response to the GapmeR’s were involved in the regulation of metabolism and inflammation and were significantly enriched for genes showing differential methylation in response to the GapmeR’s. These data indicate a significant role of DNA de novo (de)methylation in the kidney in the development of hypertension in SS rats. The findings should help to shift the paradigm of DNA methylation research in diseases involving non-dividing cells from correlative analysis to functional and mechanistic studies.